PERSEPSI TERHADAP PICTORIAL HEALTH WARNING IKLAN LUAR RUANG PRODUK ROKOK - Centurion Chandratama Priyatna; Anwar Sani (Jurnal Komunikasi, 2016)
ABSTRACTThis research emphasizes on Pictorial Health Warning (PHW) in outdoor mediaof cigarettes product’s advertisement, focusing on smoker’s perception towardspictorial health warning of “A man smoking with the skull shaped smokes”variant. This study uses qualitative descriptive method exploring the perception on theparticular pictorial health warning variant. Informants in this research arelocated in several big cities in Indonesia. The purpose of this research is toenrich the body of knowledge on health communication, especially on the dangerof smoking, and also enforcing government in the effort of communicating thehazardous of smoking towards its public.Key words: pictorial health warning, cigarette, outdoor advertisement